Polychlorinated biphenyls (PCBs) in the environment: Recent updates on sampling, pretreatment, cleanup technologies and their analysis - Reddy, A.V.B. (2019)
Polychlorinated biphenyls (PCBs) are a class of synthetic organic compounds containing carbon, hydrogen and chlorine atoms. They have been used in various industrial and commercial applications owing to their high boiling points, non-flammability, chemical stability and insulating properties. Also, PCBs are exceptionally stable and prevail in the environment for a very long time. Consequently, they may not just affect the individual organisms, but ultimately the entire ecosystems. The present review describes the sources, fate and transport of PCBs in the environment followed by their accumulation in humans, animals, plants and biota. We provide the description of current knowledge on sampling, pretreatment and cleanup procedures for the best extraction of PCBs from various contaminated sites. Further, the futuristic analytical strategies established for the determination of PCBs and adequate remedial methods are discussed in detail. Also, the analytical challenges and recommendations for future research regarding the PCBs assessment in the environment are summarized. Overall, this review presents comprehensive knowledge on cutting edge technologies available in the field of PCBs analysis. Â© 2018 Elsevier B.V.